The effects of fossil taxa, hypothetical predicted ancestors, and a molecular scaffold on pseudoextinction analyses of extant placental orders. - Peggy L Brady (Public Library of Science (PLoS), 2021)
Pseudoextinction analyses, which simulate extinction in extant taxa, use molecular phylogenetics to assess the accuracy of morphological phylogenetics. Previous pseudoextinction analyses have shown a failure of morphological phylogenetics to place some individual placental orders in the correct superordinal clade. Recent work suggests that the inclusion of hypothetical ancestors of extant placental clades, estimated by ancestral state reconstructions of morphological characters, may increase the accuracy of morphological phylogenetic analyses. However, these studies reconstructed direct hypothetical ancestors for each extant taxon based on a well-corroborated molecular phylogeny, which is not possible for extinct taxa that lack molecular data. It remains to be determined if pseudoextinct taxa, and by proxy extinct taxa, can be accurately placed when their immediate hypothetical ancestors are unknown. To investigate this, we employed molecular scaffolds with the largest available morphological data set for placental mammals. Each placental order was sequentially treated as pseudoextinct by exempting it from the molecular scaffold and recoding soft morphological characters as missing for all its constituent species. For each pseudoextinct data set, we omitted the pseudoextinct taxon and performed a parsimony ancestral state reconstruction to obtain hypothetical predicted ancestors. Each pseudoextinct order was then evaluated in seven parsimony analyses that employed combinations of fossil taxa, hypothetical predicted ancestors, and a molecular scaffold. In treatments that included fossils, hypothetical predicted ancestors, and a molecular scaffold, only 8 of 19 pseudoextinct placental orders (42%) retained the same interordinal placement as on the molecular scaffold. In treatments that included hypothetical predicted ancestors but not fossils or a scaffold, only four placental orders (21%) were recovered in positions that are congruent with the scaffold. These results indicate that hypothetical predicted ancestors do not increase the accuracy of pseudoextinct taxon placement when the immediate hypothetical ancestor of the taxon is unknown. Hypothetical predicted ancestors are not a panacea for morphological phylogenetics.